2021
DOI: 10.3390/biom11111598
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Astrocytes in Alzheimer’s Disease in the Context of the Aberrant Copper Homeostasis Hypothesis

Abstract: Evidence of copper’s (Cu) involvement in Alzheimer’s disease (AD) is available, but information on Cu involvement in microglia and astrocytes during the course of AD has yet to be structurally discussed. This review deals with this matter in an attempt to provide an updated discussion on the role of reactive glia challenged by excess labile Cu in a wide picture that embraces all the major processes identified as playing a role in toxicity induced by an imbalance of Cu in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 220 publications
(288 reference statements)
0
10
0
Order By: Relevance
“…Microglia interact with Aβ and amyloid-beta precursor protein (APP) through specific pattern-recognition receptors, including CD14, CD36, and Toll-like receptors, which are strongly expressed on the microglial surface [ 44 ]. This interaction increases microglial phagocytosis, resulting in the clearance of Aβ from the brain [ 45 , 46 ]. As an example, the phagocytic index and total Aβ load are higher in IL-1α (+) and IL-1Ra (+) microglia and microglia producing TNF-α and IL-1β are associated with a lower Aβ load and phagocytic index in AD mice [ 47 ].…”
Section: Microglia Are a “Double-edged Sword” In The Progression Of Admentioning
confidence: 99%
“…Microglia interact with Aβ and amyloid-beta precursor protein (APP) through specific pattern-recognition receptors, including CD14, CD36, and Toll-like receptors, which are strongly expressed on the microglial surface [ 44 ]. This interaction increases microglial phagocytosis, resulting in the clearance of Aβ from the brain [ 45 , 46 ]. As an example, the phagocytic index and total Aβ load are higher in IL-1α (+) and IL-1Ra (+) microglia and microglia producing TNF-α and IL-1β are associated with a lower Aβ load and phagocytic index in AD mice [ 47 ].…”
Section: Microglia Are a “Double-edged Sword” In The Progression Of Admentioning
confidence: 99%
“…Copper (DB09130) is a transition metal and a trace element in the body. Copper imbalance is associated with the pathogenesis of AD, which is an avenue for new therapeutic strategies (Ejaz et al, 2020 ; Zhu et al, 2020 ; Zubčić et al, 2020 ; Lei et al, 2021 ; Pal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[88] This interaction promotes phagocytosis, leading to the clearance of A𝛽 from the brain. [89,90] Microglia producing TNF-𝛼 and IL-1𝛽 have shown higher phagocytic activity in AD mice. [91] Strategies aimed at modulating microglial activation by inhibiting the release of inflammatory factors are highly desired, and in this regard, preclinical studies have demonstrated that blocking TNF or IL-1 receptors through genetic or pharmacological approaches can reduce amyloid pathology and tau phosphorylation.…”
Section: Microglia Role In Alzheimer's Diseasementioning
confidence: 99%